Optimalisasi Kualitas Pembelajaran Bahasa Indonesia Melalui Penerapan Model Pembelajaran Berbasis Siklus dengan Distribusi Permasalahan Kontekstual - Ni Wayan Sudarti (UHN IGB Sugriwa Denpasar, 2017)
This study aims to: (1) to determine the effectiveness of the model-based learning cycle by providing contextual problems can motivate learning Indonesian in class X MM1 SMK Negeri 1 Sukawati, (2) to identify any obstacles obtained in the application-based learning model cycle with the provision of contextual issues, in class X MM1 SMK Negeri 1 Sukawati. This research uses descriptive qualitative data analysis and classroom action research (PTK). This research method using two cycles, each cycle consisting of planning, action, observation and reflection stages. The data is the data analyzed motivation and learning outcomes. Broadly speaking, the average percentage of the observation of motivation 70.2% in the first cycle increased to 80.2% in the second cycle means an increase of 10% in the second cycle. While based on the analysis of student questionnaire presentation success action diproleh 76.1% in the first cycle increased to 78.84 in the second cycle, means an increase of 2.74% in the second cycle. Judging from individual mastery, the first cycle reaches 81% means that students who obtain above or equal to 75, as many as 26 out of 32 students, the remaining 6 students, or 18% incomplete. While on the second cycle, the percentage of individual mastery has been increased, the second cycle of individual completeness reached 93.8% means that students who received grades above or equal to 75, as many as 30 people and 2 students or 6.25% of students have not been completed. This means an increase of individual mastery of the first cycle to the second cycle of 11.75% or 4 students. For classical completeness on the first cycle is 81% increased to 93.8% in the second cycle, meaning an increase by 12.8% in the second cycle. From this study it can be concluded that: (1) The application of the model-based learning cycle by providing contextual problems can increase students' motivation class X MM1 SMK Negeri 1 Sukawati, with the material of the Indonesian language discourse. This can be seen in the increase in the observation of students 70.2% in the first cycle and increased to 80.2% in the second cycle. (2) Barriers acquired in the application of learning models berbasisis cycle in class X MM1 SMK Negeri 1 Sukawati, can be solved, it is evident from the results achieved in the classical completeness, ie 81% in the first cycle, increased to 93.8% in the second cycle.